Peran Mutu Sumberdaya Manusia PMA dan PMDN Penyerapan Tenaga Kerja di Indonesia - Hesty Nopiana Dewi; Syahrituah Siregar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research was conducted to analyze (1) whether the quality of human resources, foreign investment, domestic investment affects employment in Indonesia; (2) what is the dominant variable influencing jobs in Indonesia.        This study indicates that the regression analysis made shows that all dependent variables, such as the quality of the human resource, foreign investment, and domestic investment, affect Indonesia's labor absorption. Foreign investment has become the most dominant variable. It has a significant effect on the independent variable, namely the total workforce on employment in Indonesia. Indonesia is still very dependent on foreign investment, entering Indonesia to accelerate economic growth and absorb more workers again in Indonesia.